KEEFEKTIFAN TEKNIK MEMBACA SKIMMING DALAM MENINGKATKAN PEMAHAMAN MEMBACA (PENELITIAN EKSPERIMEN PADA MATA KULIAH DOKKAI SAKUBUN 5 MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG ANGKATAN 2016/2017) - Widyaningrum, Stephanie; Hadriana, Hadriana; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The lack of motivation of students in learning Dokkai is due to monotonous learning methods, lack of mastery of kanji, vocabulary that does not know its meaning and text that is too long. The purpose of this study was to determine the effect of skimming techniques on students' ability to read Japanese text comprehension (dokkai) by students from the Japanese Ministry of Education, Faculty of Teacher Training and Teacher Education, University of Riau. skimming techniques is a strategy to improve students' reading comprehension skills with stages that will guide students to understand the text to read well. This study used quasi-experimental research with the design of one group pretest-posttest. The object of this study were 28 third grade students from Japanese Teacher Education, Department of Education and Education, University of Riau 2016/2017 Academic Year. Data collection is done by giving a test. The test given is 10 essays to determine students' ability to read comprehension (pretest and posttest). The average pretest results obtained by students were 58.75 and in posttest it increased 26.96 to 85.71. So there is a significant impact by applying skimming techniques to learn Japanese reading comprehension by students from the Japanese Ministry of Education, Faculty of Teacher Training and Education, University of Riau. Thus, it can be concluded that the cursory reading technique is effective for improving the ability to read Japanese text.Key Words: Dokkai, Skimming, The effectiveness.